Interaction of language and culture in the process of international education (Eurasian Journal of Philology Science and Education, 2023)
The relationship between language and culture can be seen as a relationship between part and whole. Language can be perceived as a component of culture and as an instrument of culture. It interacts with every aspect of human life in society, can be understood only if it is considered in relation to society. However, language is at the same time free in relation to culture as a whole, and it can be considered as an independent semiotic system, i.e. apart from culture, which is done in traditional linguistics. According to our concept, since every native speaker is at the same time a bearer of culture, linguistic signs acquire the ability to perform the function of cultural signs and thereby serve as a means of representing the main cultural attitudes. That is why the language is able to reflect the cultural and national mentality of its speakersEducation in its turn is a cultural process to make human beings better and meaningful, while human beings will produce good culture if supported by broad education. In this context, education cannot be separated from culture and culture cannot be separated from education. Education is defined as a teaching-learning process that familiarizes the citizens as early as possible to explore, to understand, to realize, to master, to live, and to practice all agreed values as a worthy and desirable value, and useful for the life and development of the individual, and country. Thus, the process of international education involves different disciplines, reflecting in one way or another relationship of language and culture: sociolinguistics, ethnolinguistics, language and cultural studies.